Determinant of green value on corporate tax avoidance - Sailendra, Sailendra (WIM Solusi Prima, 2024)
This study investigates the relationship between green value and tax avoidance, with a focus on the moderating role of intellectual capital. Using a sample of 264 firm-year observations from Indonesian listed companies between 2017 and 2022, we employ panel data regression analysis to examine these relationships. Our findings reveal that while green value does not have a significant direct effect on tax avoidance, intellectual capital plays a crucial role both as a direct determinant and as a moderator. Specifically, we find that higher intellectual capital is associated with lower tax avoidance, suggesting that firms with strong intellectual resources tend to engage in more responsible tax practices. However, the positive moderating effect of intellectual capital on the relationship between green value and tax avoidance indicates that firms with high intellectual capital may be more adept at leveraging their environmental initiatives for efficient tax planning. These results highlight the complex interplay between environmental commitment, intellectual resources, and tax strategies in modern corporations. Our study contributes to the growing literature on corporate sustainability and tax behavior, offering implications for policymakers in designing tax regulations and environmental incentives, and for managers in strategically managing intellectual capital for both environmental and tax efficiency purposes.